Beach house reunion [large type] - Monroe, Mary Alice (Monroe, Mary Alice. Beach house series., 2018)
At Cara Rutledge's home on Isle of Palms, everything is comfortingly the same, yet rife with painful memories. Only through reconnecting with family, friends, and the rhythms of the lowcountry can Cara release the hold of the past and open herself to the possibility of a new love, career, and hope for the future. Meanwhile, her niece Linnea, a recent college graduate who doesn't know where her life will take her, leaves her historic home in Charleston, with all its entitlement and expectations, and heads to her aunt's beach house. On the island, she is part of the freer, natural ocean lifestyle she loves, rejoining the turtle team, learning to surf, and falling in love. Remembering the lessons of her beloved grandmother, Lovie, the original "turtle lady," Linnea rediscovers a meaningful purpose to her life and finds the courage she needs to break from tradition.